Great economists since Keynes : an introduction to the lives & works of one hundred modern economists - Blaug, Mark. (Brighton, Sussex : Wheatsheaf Books : Distributed by Harvester Press, 1985)
This book describes the careers and contributions of 100 famous economists, who have left ineradicable marks on twentieth-century economics.
Includes bibliographical references and indexes.
lje 20/4/18
Loans
Keywords: Economists; Economics